Labrador on the lawn - Daniels, Lucy. (New York : Scholastic, 2004)
While on vacation Mandy and James find a stray mischievous Labrador, but the dog has no identification tags and they don't know how to find the owner.
"An Apple paperback."
810
Accelerated Reader AR
Keywords: Labrador retriever -- Fiction; Dogs -- Fiction